Association of Pre-ECT Anxiety Symptoms With Electroconvulsive Therapy Treatment Efficacy in Schizophrenia - Birong Chen; Hasvinjit Kaur D/O Gulwant Singh; Nisha Chandwani; Jonathan Jie Lee; Shih Ee Goh; Xiao Wei Tan (The Journal of ECT, 2026)
Objectives: Pre-ECT anxiety symptoms are common among patients undergoing Electroconvulsive Therapy (ECT). In this retrospective observational cohort study, we aim to explore the association between pre-ECT anxiety symptoms and ECT treatment outcomes in patients with schizophrenia. Methods: We conducted a retrospective analysis of 979 patients with schizophrenia or schizoaffective disorder who received ECT at a tertiary public psychiatric hospital in Singapore. Patients were categorized into two groups based on the mean value of pre-ECT Brief Psychiatric Rating Scale (BPRS) anxiety subdomain score: with anxiety (>6) and without anxiety (≤6). Changes in clinical outcomes were measured using BPRS-psychotic, BPRS-anxiety, BPRS-negative and BPRS-manic subscale, Global Assessment of Functioning, Clinical Global Impression-improvement (CGI-I), EuroQoL-5 Dimension Visual Analogue Scale (EQ-5D-VAS) and Montreal Cognitive Assessment (MoCA) scale. Associations between the pre-ECT anxiety scores and patient sociodemographic, psychiatric symptom subscales, and functional assessments were analyzed. Results: Younger age, a history of ECT, and concurrent antidepressant use were significantly associated with pre-ECT anxiety symptoms. Higher pre-ECT anxiety scores were positively correlated with psychotic, negative, and manic symptom severity, and were negatively correlated with general functioning and subjective quality of life (EQ-5D-VAS) ( P